Mechanical properties and structure‐function relationships of human chondrocyte‐seeded cartilage constructs after in vitro culture. Issue 10 (20th March 2017) - Middendorf, Jill M.; Griffin, Darvin J.; Shortkroff, Sonya; Dugopolski, Caroline; Kennedy, Stephen; Siemiatkoski, Joseph; Cohen, Itai; Bonassar, Lawrence J.
ABSTRACT: Autologous Chondrocyte Implantation (ACI) is a widely recognized method for the repair of focal cartilage defects. Despite the accepted use, problems with this technique still exist, including graft hypertrophy, damage to surrounding tissue by sutures, uneven cell distribution, and delamination. Modified ACI techniques overcome these challenges by seeding autologous chondrocytes onto a 3D scaffold and securing the graft into the defect. Many studies on these tissue engineered grafts have identified the compressive properties, but few have examined frictional and shear properties as suggested by FDA guidance. This study is the first to perform three mechanical tests (compressive, frictional, and shear) on human tissue engineered cartilage. The objective was to understand the complex mechanical behavior, function, and changes that occur with time in these constructs grown in vitro using compression, friction, and shear tests. Safranin‐O histology and a DMMB assay both revealed increased sulfated glycosaminoglycan (sGAG) content in the scaffolds with increased maturity. Similarly, immunohistochemistry revealed increased lubricin localization on the construct surface. Confined compression and friction tests both revealed improved properties with increased construct maturity. Compressive properties correlated with the sGAG content, while improved friction coefficients were attributed to increased lubricin localization on the construct surfaces. In contrast, shear properties did not improve with increased culture time. This study suggests the various mechanical and biological properties of tissue engineered cartilage improve at different rates, indicating thorough mechanical evaluation of tissue engineered cartilage is critical to understanding the performance of repaired cartilage. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2298–2306, 2017.